EVALUATING RENAL TIME-INTEGRATED ACTIVITY COEFFICIENT IN [177Lu]Lu-DOTA-TATE THERAPY: SIMULTANEOUS VS. SEPARATE KIDNEY MODELING USING NON-LINEAR MIXED-EFFECTS MODELING - Indra Budiansah; Assyifa Rahman Hakim; Fira Dwi Ananda; Supriyanto Ardjo Pawiro; Deni Hardiansyah (Joint Prosiding IPS dan Seminar Nasional Fisika, 2026)
This study aimed to compare renal time-integrated activity coefficients (TIACs) in [177Lu]Lu-DOTA- TATE therapy using non-linear mixed-effects modeling (NLMEM), by evaluating the effect of the fitting setting method of left and right kidney biokinetic data to TIAC calculation. Renal biokinetic data of [177Lu]Lu-DOTA-TATE were collected from ten patients with neuroendocrine tumors from literature (PMID:33443063). SPECT/CT imaging was performed between days 1 and 7 after-injection. The bi-exponential function parameters were fitted to biokinetic data using NLMEM performed using NONMEM software, with two fitting approaches: simultaneous fitting of both kidneys and separate fitting of the left and right kidneys. TIACs from the simultaneous fitting were defined as simultaneous TIACs (siTIACs), and those from separate fitting as separated TIACs (seTIACs). The differences between siTIACs and seTIACs were assessed using relative deviations (RDs), with seTIACs considered equivalent to siTIACs if RD was below 5%. The bi-exponential function successfully describes the renal biokinetic data. seTIACs showed good agreement with the siTIACs, with median[min, max] RD of -1.6[-4.5, 0.8]%. Simultaneous fitting of left and right kidneys biokinetic data using the NLMEM approaches produced similar TIACs to those obtained from separate fittings. Therefore, TIACs from simultaneous and separate fittings of renal biokinetic data are comparable and clinically applicable.